Sports preferences in children and adolescents in psychiatric care-evaluation of a new questionnaire - Florian Breido; Florian Breido; Sebastian Stumm; Ekkehart Jenetzky; Ekkehart Jenetzky; Michael Huss (Frontiers Media S.A., 2024)
IntroductionAs part of an exploratory and hypothesis-generating study, we developed the Sports Preference Questionnaire (SPOQ) to survey the athletic behavior of mentally ill children and adolescents, subjectively assessed physical fitness and perceived psychological effects of physical activity.MethodsIn a department of child and adolescent psychiatry, we classified 313 patients (6-18 years) according to their primary psychiatric diagnosis. The patients or-in the parental version of the questionnaire-their parents reported their sport preferences on the SPOQ. As possibly influential factors, we also assessed the frequency of physical activity, the importance of a trainer, coping with everyday life through physical activity, and subjectively perceived physical fitness.ResultsOne in 3 patients (32.4%) stated that they were not physically active. Patients diagnosed with eating disorders reported, on average, a notably high frequency (median of 3 h/week) and degree of coping with daily life through physical activity (median of 5 on a 6-point Likert scale). Patients with anxiety disorders and depression had the lowest self-perception of physical fitness (mean value of 3.1 or 3.7 on an interval scala from 0 to 9). The presence of a trainer was generally considered not important, except for ADHD patients (median of 3 on a 6-point Likert scale).ConclusionThe SPOQ is sensitive for differential effects of core child and adolescent disorders as well as for main covariates influencing the complex association between physical activity and emotional and behavioral disorders in children and adolescents. Based on this pilot study, we discussed the need for an efficacy study to measure the effects of sports therapy.